Co, N, S-Codoped Three-Dimensional Graphene as Efficient Bi-Functional Electrocatalyst for Oxygen Reduction/Hydrogen Evolution Reaction. Issue 12 (11th August 2017) - Wang, Shumin; Qin, Yong; Liu, Yang; Chu, Fuqiang; Kong, Yong; Tao, Yongxin
Abstract : Co, N, S-codoped three-dimensional graphene (Co, N, S/3DG) has been fabricated using Co(SCN)2 as the precursor. It has been found that Co, N, S/3DG is a highly efficient bi-functional electrocatalyst for oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER). It exhibits the high catalytic activity comparable to the Pt/C catalyst toward ORR, and the low overpotential of 260 mV to afford the current density of 10 mA cm −2 toward HER. The doping of S can promote the electrocatalytic performance of Co, N-codoped graphene due most likely to the defects induced by sulfur atom. The results provide new clues to design multi-functional electrocatalyst in energy storage and conversion.